ENHANCE ENGLISH LANGUAGE LEARNING STUDENT BASED ON GOOGLE CLASSROOM - Yossy Fadly; Doni Efrizah; Dedi Purwanto; Yurika Aulia (Sean Institute, 2023)
This research relates to the application of Google Classroom in learning English in the Accounting Study Program at Pembangunan Panca Budi University. The aim is to find out the effect of using Google Classroom in supporting English learning. Respondents consisted of active students from class 2019, 2020, 2021 and 2022 who had used Google Classroom in semesters 1 and 2. The data collection method used was a research questionnaire whose data was analyzed using the SPSS program. The results of this study show that there is no significant effect of the convenience of Google Classroom and student expectations on the use of Google Classroom in supporting English learning. Meanwhile, for the performance of Google Classroom and social influence on the use of Google Classroom, there is a significant influence.